Improving Performance of Universities Using University Rankings. Case Study, Al Farabi Kazakh National University, Kazakhstan - Serban Agachi (University Babes-Bolyai, 2017)
Starting from personal experience and expertise, this article discusses the relevance of international rankings for improving the individual performance of universities. After analyzing the most relevant indicators used by one such ranking, the article suggests possible solutions to be considered by one individual university (i.e. Al Farabi Kazakh National University) if it aims to improve its position in international league tables and the quality of the processes in the university. At the same time, the article debates the degree to which the indicators used by the afore-mentioned international ranking are still relevant and can still be useful at institutional level, for university leaders.